PENAFSIRAN HAKIM PENGADILAN NEGERI ATAS BARANG SITAAN TINDAK PIDANA UNTUK DIMUSNAHKAN - Dimas Farlyanda Prathama; Firman Wijaya (Fakultas Hukum Universitas Tarumanagara, 2020)
This research is motivated because confiscated goods that still have value should be appropriate to support those who are entitled in this case the representatives or victims who litigate and seek justice in court. The State and the Government are obliged to provide legal protection and provide equality from all classes of society, because all are equal before the law (equality before the law). The vonnis's fall was one of the most difficult things a judge had to change. The problem that will be discussed in this discussion is whether the consideration of the South Jakarta District Court Panel of Judges asks that a follow-up seized item cannot be discussed or must be destroyed? Subsystems of juridical meaning or legal system that are listed in a relatively intact system, carried away by their nature to meet the needs of the community make the system open. There are two structuring principles that build systems in the legal system, namely the principle of external or formal structuring and the principle of internal or material structuring. After completing this thesis, the researcher can conclude that the confiscated goods still have the value of benefits to compensate or save to save in accordance with applicable KUHAP rules.